Penerapan Pendidikan Karakter Terhadap Prestasi Belajar Mata Pelajaran Produktif Siswa di SDIT Tawakkal Pacitan - Siti Komariyah; Mokhamad Choirul Hudha (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Character education is a conscious and planned effort to instill values ​​so that they are integrated in students so that they can realize good behavior and attitudes. This research aims to determine whether there is an influence of character education on students' productive learning achievement in subjects at the Tawakkal Integrated Islamic Elementary School. This research used a qualitative descriptive approach through data collection and was carried out in class 3A SDIT Tawakkal Pacitan. Data collection techniques in this research were interviews and documentation. Analysis of interview data was used as the main data for drawing conclusions in this research and analysis of documentation data in the form of photos of learning activities, students' daily tests and activities at school during the time this research took place.